2018
DOI: 10.1039/c7cp07891a
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline-earth (Be, Mg and Ca) bonds at the origin of huge acidity enhancements

Abstract: Conventional bases become very strong acids upon association with alkaline-earth derivatives MX2 (M = Be, Mg and Ca).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
(25 reference statements)
3
27
0
Order By: Relevance
“…The reason behind this huge effect on the water acidity relies on the large binding energy differences between neutral and charged complexes. Previous works,,,,, have shown precisely that this binding enthalpy difference is related to the acidity enhancement through a thermodynamic cycle analogous to the one shown in Scheme .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The reason behind this huge effect on the water acidity relies on the large binding energy differences between neutral and charged complexes. Previous works,,,,, have shown precisely that this binding enthalpy difference is related to the acidity enhancement through a thermodynamic cycle analogous to the one shown in Scheme .…”
Section: Resultsmentioning
confidence: 82%
“…It is well‐known that in molecular clusters linked by hydrogen bonds, from dimers onwards, the thermodynamic acid‐base properties of the terminal monomers are substantially modified, as for instance in (HCN) n and (HNC) n . We have reported the possibility of modulating the acidity of imidazoles and pyrazoles by means of beryllium bonds; the huge acidity increases produced by alkaline‐earth bonds; the large proton affinity (PA) enhancements triggered by non‐covalent interactions; and the changes on the acidity and basicity of disiloxane due to the formation of complexes with Lewis acids and Lewis bases …”
Section: Introductionmentioning
confidence: 99%
“…The lithium bond may be probably classified as the σ‐hole bond however it is characterized by numerous unique properties . For the elements of group 2 the beryllium bond and the magnesium bond were analysed but they were not rather classified as the σ‐hole or π‐hole bonds. In a recent study the regions of the positive electrostatic potential were discussed in various moieties where Mg‐centre was characterized by different coordination, up to six …”
Section: Introductionmentioning
confidence: 99%
“…In another study different approaches were used to describe the magnesium bond; QTAIM, the ELF (Electron Localization Function) method and the NBO (Natural Bond Orbital) method. Very recently the beryllium, magnesium and calcium divalent centres were discussed which interact with the Lewis base species that leads to deformations of initial linear structure of their corresponding moieties …”
Section: Introductionmentioning
confidence: 99%
“…Even more recently interesting cases were described in which a network of conjugated bonds strongly hinders a hydrogen bond, phenomenon which was called Resonance Impaired Hydrogen Bonds (RIHB) [20]. Also recently, it was shown that Mg can also yield magnesium bonds similar to the beryllium ones [21]; but, what is more important and unexpected, in some specific cases the magnesium bonds were found to be of similar strength or even stronger than the beryllium bond analogues [22]. The question we would like to address in this paper is whether the intramolecular magnesium bonds also share some similarities with the corresponding intramolecular beryllium bonds and if some dissimilarities appear, what is the origin.…”
Section: Introductionmentioning
confidence: 99%